2009
DOI: 10.1002/jcp.21920
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RIZ1 protein (Retinoblastoma‐interacting zinc‐finger protein 1) in prostate cancer epithelial cells changes with cancer grade progression and is modulated in vitro by DHT and E2

Abstract: The nuclear protein methyl-transferase Retinoblastoma-interacting zinc-finger protein 1 (RIZ1) is considered to be a downstream effector of estrogen action in target tissues. Silencing of RIZ1 expression is common in many tumors. We analyzed RIZ1 expression in normal and malignant prostate tissue and evaluated whether estradiol (E2) or dihydrotestosterone (DHT) treatment modulated RIZ1 in cultured prostate epithelial cells (PEC). Moreover, we studied the possible involvement of RIZ1 in estrogen action on the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…Stimulation by androgens or estradiol couples classical steroid receptors to cytosolic signaling pathways and cell proliferation through the induction of an ER-AR-src ternary complex in LNCaP (Migliaccio et al, 2000) and EPN (Chieffi et al, 2003). Recently, we demonstrated that E2 treatment inhibited cell proliferation of EPN cells involving retinoblastoma-interacting zinc-finger protein 1 (RIZ1; Rossi et al, 2009), which is a downstream effector of ER activation in target tissues (Medici et al, 1999;Abbondanza et al, 2000;Gazzerro et al, 2006). In present study, we found a rapid transient activation of ERK1/2 after RAL treatment in EPN cells and a more sustained and prolonged ERK1/2 activation in CPEC.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Stimulation by androgens or estradiol couples classical steroid receptors to cytosolic signaling pathways and cell proliferation through the induction of an ER-AR-src ternary complex in LNCaP (Migliaccio et al, 2000) and EPN (Chieffi et al, 2003). Recently, we demonstrated that E2 treatment inhibited cell proliferation of EPN cells involving retinoblastoma-interacting zinc-finger protein 1 (RIZ1; Rossi et al, 2009), which is a downstream effector of ER activation in target tissues (Medici et al, 1999;Abbondanza et al, 2000;Gazzerro et al, 2006). In present study, we found a rapid transient activation of ERK1/2 after RAL treatment in EPN cells and a more sustained and prolonged ERK1/2 activation in CPEC.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we used the EPN prostate cell line, which expresses functional AR and both ERs (Sinisi et al, 2002;Rossi et al, 2009). EPN cells resulted by an apparently spontaneous adaptation to indefinite growth in vitro of primary cultures of epithelial prostate cells derived by normal tissue isolated from a prostate sample collected after radical prostatectomy for cancer.…”
Section: Prostate Cell Cultures and Prostate Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations